SOLUSI INOVATIF: MENGUBAH SAMPAH KERING MENJADI BRIKET UNTUK ENERGI ALTERNATIF BERKELANJUTAN DI KEBUN BELIMBING NGRINGINREJO BOJONEGORO - Destiana, Annisa; Alfianti, Atika; Sania, Chadlirotus; Firnanda, Titia Juwita Ayu; Firmansyah, Aditya Eka; Setyaningrum, Dyah (Universitas Mataram, 2025)
The ongoing energy crisis encourages the search for environmentally friendly and economical alternative energy sources. Ngringinrejo Village, Bojonegoro, produces organic waste such as dry leaves and twigs from starfruit gardens, which remain underutilized and pose environmental risks. This community service activity aims to introduce appropriate technology through the production of briquettes from dry waste as an alternative energy source. The methods used included field surveys, literature studies, and hands-on training for local residents. The briquette-making process involves carbonization, grinding, mixing with coconut shell and tapioca adhesive, molding with a semi-mechanical tool, and drying. The training involved around 90 participants, including village officials, students, youth organizations, and community leaders. The activity resulted in increased community knowledge of waste management and the benefits of briquettes as an energy source. The produced briquettes are environmentally friendly, economically valuable, and provide new economic opportunities. This activity also fostered environmental awareness and social collaboration. In conclusion, briquettes made from dry waste offer a viable energy solution that supports circular economy practices at the village level.